Research on security protection of unmanned aerial vehicle systems based on zero trust - Ji Shengkai; Yang Zhiming; Zhao Jiankun; Li Bin; Huang Yilong (Dianzi Jishu Yingyong)
In recent years, unmanned aerial vehicles (UAVs) have been widely used in the military and civilian fields, especially since the Russia-Ukraine conflict, their advantages of low cost and strong functions are particularly prominent and have played a huge role. However, the usage environment of drones is complex and often uncontrollable, facing more serious security threats such as drone hijacking, network attacks, wireless communication interference, malicious access, and data theft. In response to these risks, traditional security measures such as wireless network security and data encryption are currently mainly adopted in drone systems. The zero trust architecture, as a new security model, emphasizes dynamic trust and provides new ideas for the security protection of unmanned aerial vehicle systems. This paper researches on zero trust security protection architecture, combined with typical applications of unmanned aerial vehicle systems, analyzes the security risks faced by unmanned aerial vehicle measurement and control, data transmission, and proposes a zero trust based unmanned aerial vehicle system security protection architecture to address these risks. It designs implementation solutions for zero trust technology in unmanned aerial vehicle measurement and control, data communication, and typical scenarios, providing strong support for the specific implementation of zero trust architecture in military and civilian unmanned aerial vehicle systems.